If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 11 = 100 Reorder the terms: 11 + 2x = 100 Solving 11 + 2x = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 2x = 100 + -11 Combine like terms: 11 + -11 = 0 0 + 2x = 100 + -11 2x = 100 + -11 Combine like terms: 100 + -11 = 89 2x = 89 Divide each side by '2'. x = 44.5 Simplifying x = 44.5
| 7-5x=x | | F(x)=7x-3x | | x+7=7x-17 | | 6x+2-3x=1 | | a+b^3= | | a/4=8=13 | | 2x/0.2-x=7.03 | | (x/2)-(x/5) | | 4x-12=10x | | 2(x+3)-11=x+5 | | 4x3/8 | | 2x+14=3x+2 | | t=2t-3(1-t) | | 4x+28=2x-1 | | a(1-x)=2ax+3-2a | | 4x-28=5x-40 | | 2(3x-5)+7=33 | | 3w-4=17 | | log16x=5/2 | | ax=a-b+bx | | -5(x-2)=40 | | -2x=1/7 | | 3u-1=14 | | 4x^3+2x^2+(-8x)+3=0 | | C=7n+2(n-1) | | -4(-3w+v)+4(-6v+6w)= | | 10-4t=-2 | | s+14=31 | | X/8-2.1=-14.9 | | -7x+5=3(x-5) | | (x+1)(3x+1)=5 | | (x-1)(3x+1)=5 |